Studi Analisis Permasalahan Permainan Outdoor Di Taman Kanak-Kanak Negeri Pembina Muara Bulian - Adinda Sabrina Hani; Ani Sartika Sari; Asih Nur Ismiatun; Melisa Kotrun Nada; Siti Annisa Aszari (Jurnal Teknologi Pendidikan Dan Pembelajaran | E-ISSN : 3026-6629, 2024)
Outdoor games (outdoor games), outdoor play is a learning process through play activities that take place outside, which is important for training children's gross motor skills.  This research aims to find out the problems that exist in outdoor games at TK N Pembina Muara Bulian.  This research uses qualitative descriptive.  The method used in this research was observation and interviews in 5 meetings, each meeting session was given 45 minutes for implementation.  The subjects of this research were students at Kindergarten N Pembina Muara Bulian.  The data analysis technique used in this research uses observation and interviews, and the results obtained in this research show that there are several problems that occur in outdoor games at the Pembina Muara Bulian State Kindergarten.